Cyclic RGD functionalized liposomes targeted to activated platelets for thrombosis dual-mode magnetic resonance imaging. Issue 3 (13th December 2019) - Ye, Sen; Liu, Yang; Lu, Yi; Ji, Yuqin; Mei, Lianlian; Yang, Mingwen; Gong, Xiaoxuan; Gu, Qian; Li, Di; Yang, Fang; Li, Chun-Jian
Abstract : Thrombotic disease is a serious threat to human health. Abstract : Thrombotic disease is a serious threat to human health. The rapid and accurate detection of thrombosis is still a clinical challenge. To achieve the accurate diagnosis of thrombosis with magnetic resonance imaging (MRI), nanomaterials-based contrast agents have been developed in recent years. In this study, cyclic RGD functionalized liposomes targeted to the activated platelets are developed for thrombosis dual-mode MRI. The cyclic RGD functionalized liposomes (cRGD@MLP-Gd) encapsulated with gadolinium diethylenetriamine penta-acetic acid (Gd-DTPA) and superparamagnetic iron oxide (SPIO) are prepared, and their thrombus-targeted T 1 and T 2 MRI potential is evaluated in vitro and in vivo . Results show that cRGD@MLP-Gd could actively bind to the activated platelets and gradually accumulate at the thrombus site with a T 1 − T 2 contrast enhancement imaging effect in vitro . In in vivo MRI experiments, cRGD@MLP-Gd exhibits a T 2 contrast enhancement at 1 h after intravenous administration, followed by a visibly larger T 1 contrast enhancement at the thrombus site. This dynamic property showed that cRGD@MLP-Gd could actively bind to thrombus and possessed an enhanced T 1 and T 2 dual-mode MRI effect in vivo . Our results establish the characterization, feasibility and superiority of cRGD@MLP-Gd for the rapid identification of thrombosis, showing great potential to improve diagnostic accuracy and sensitivity to thrombosis of the MRI technique.